ARBUSCULAR MYCORRHIZAL FUNGI AND GLOMALIN-SOIL RELATED PROTEIN IN DEGRADED AREAS AND REVEGETATED WITH EUCALYPT AND WATTLE - Silva, Cristiane Figueira da (2012)
http://dx.doi.org/10.5902/198050987556The objective of this study was to evaluate the influence of revegetation with  Eucalyptus camaldulensis and Acacia mangium in pure and mixed stands in the composition and mycorrhizal fungi diversity (AMF), as well as in the production of glomalin-related soil protein (GRSP) of an area degraded by clay extraction. The experimental design used was randomized complete block with four treatments (pure stands Eucalyptus camaldulensis and Acacia mangium; mixed Eucalyptus camaldulensis + Acacia mangium; and covered with spontaneous vegetation – ADVE) and three replications. Soil samples were collected at 0-5 cm soil layer in each plot. The spores were extracted and taxonomically identified. Relative density, frequency of each species and the Shannon-Wiener, Pielou and Simpson indexes were analyzed. The GRSP (total glomalin – TG and easily extractable glomalin - EEG) was extracted with sodium citrate and quantified by the Bradford method. Abundance of AMF was higher in the degraded areas covered by weeds (spontaneous vegetation) compared to plantations; however, it showed lower species diversity. The areas of eucalypt monoculture showed a lower level of AMF diversity in relation to areas of eucalypt intercropped with Acacia. The genera Glomus and Acaulospora were the AMF, with the largest number of species. The GRSP was closely correlated with soil C and N, which observed in greater amounts in plantations in relation to the sites covered with spontaneous vegetation. Revegetation of clay extraction site promoted the reduction of AMF sporulation, while the diversity and production GRSP increased.